PENGARUH MODEL PROJECT BASED LEARNING (PJBL) DALAM PENGUATAN PROYEK PROFIL PELAJAR PANCASILA TERHADAP PEMBENTUKAN KARAKTER PESERTA DIDIK SD MUHAMMADIYAH MIMBAR - Annisa Maqfira; Nursalam; Syarifah Aeni Rahman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The research is a quantitative research with a pre-experimental one group pretest-posttest design that aims to determine the application of the Project-based Learning (PjBL) model in the Pancasila Student Profile Strengthening Project (P5), to determine the differences in student character before and after the application of the Project-based Learning model, and to analyze the influence of the Project-based Learning model on the character formation of students at Muhammadiyah Mimbar Elementary School. The research subjects were 19 students of class IV B involved in a project with the theme "Sustainable Lifestyle". Collected through (pretest and posttest) and observation sheets focusing on the dimensions of mutual cooperation, global diversity, and creativity, then analyzed with descriptive statistics and t-test Paired Sample T-Test using SPSS Statistics 22. The results showed the average pretest character of students was 62.9 with a distribution of sufficient categories of 63.16% and good 36.84%, none had reached the very good category or exceeded the KKTP 75. After treatment by applying the Project-based Learning (PjBL) model, the average posttest score increased to 82.63 with 68.42% of students in the very good category and 31.58% in the good category, so that all students achieved learning completeness according to KKTP. The Paired Sample T-Test test produced a t value = 13.324 with Sig. (2-tailed) = 0.000 < 0.05, so H0 is rejected and H1 is accepted, meaning there is a significant influence of the implementation of the Project-based Learning (PjBL) model in strengthening the Pancasila Student Profile Project on the character formation of grade IV B students of Muhamamdiyah Mimbar Elementary School. Thus, the implementation of the Project-based Learning (PjBL) model in strengthening the Pancasila student profile project is effective in strengthening the character of students, especially the aspects of mutual cooperation, global diversity, creativity through holistic, contextual, student-centered, and exploratory learning experiences according to the principles of the Independent Curriculum.